Acylsugar protection of Nicotiana benthamiana confers mortality and transgenerational fitness costs in Spodoptera litura - Wang, Ran; Gao, Bingli; Zhang, Qinghe; Zhang, Ziyi; Li, Yunyi; Yang, Qingyi; Zhang, Mi; Li, Wenxiang; Luo, Chen (Frontiers in Plant Science, 2022)
Acylsugars are secondary metabolites that are produced in the trichomes of some solanaceous species and can help control several herbivorous insect pests. Previously, knockout mutations (asat2 mutants) were shown to significantly reduce the acylsugar content of Nicotiana benthamiana, and significantly improve the fitness of six generalist insect herbivores. The current study compared the significant mortality and fitness costs in Spodoptera litura conferred by acylsugar protection of N. benthamiana (wild-type plants) compared to S. litura strains reared in acylsugar-deficient plants with depleted acylsugar biosynthesis. Acylsugar protection prolonged the developmental duration and decreased viability in the larval stages. Further, the fecundity of females and the hatching rate of eggs significantly decreased under acylsugar protection. For F1 offspring, acylsugar protection still exerted significant negative effects on larval survival rate and fecundity per female. The net reproductive rate and relative fitness of the S. litura strain were strongly affected by acylsugar. Altogether, these results indicate that acylsugar could contribute to plant protection due to toxicity to pests, diffused availability, and low environmental persistence. This could represent a complementary and alternative strategy to control populations of insect pests.